Modelling the Antarctic Ice Sheet across the mid-Pleistocene transition - Implications for Oldest Ice - Sutter, Johannes; Fischer, Hubertus; Grosfeld, Klaus; Karlsson, Nanna N.B.; Kleiner, Thomas; Van Liefferinge, Brice; Eisen, Olaf (2019)
The international endeavour to retrieve a continuous ice core, which spans the middle Pleistocene climate transition ca. 1.2-0.9 Myr ago, encompasses a multitude of field and model-based pre-site surveys. We expand on the current efforts to locate a suitable drilling site for the oldest Antarctic ice core by means of 3-D continental ice-sheet modelling. To this end, we present an ensemble of ice-sheet simulations spanning the last 2 Myr, employing transient boundary conditions derived from climate modelling and climate proxy records. We discuss the imprint of changing climate conditions, sea level and geothermal heat flux on the ice thickness, and basal conditions around previously identified sites with continuous records of old ice. Our modelling results show a range of configurational ice-sheet changes across the middle Pleistocene transition, suggesting a potential shift of the West Antarctic Ice Sheet to a marine-based configuration. Despite the middle Pleistocene climate reorganisation and associated ice-dynamic changes, we identify several regions conducive to conditions maintaining 1.5 Myr (million years) old ice, particularly around Dome Fuji, Dome C and Ridge B, which is in agreement with previous studies. This finding strengthens the notion that continuous records with such old ice do exist in previously identified regions, while we are also providing a dynamic continental ice-sheet context. SCOPUS: ar.j info:eu-repo/semantics/published